Cover Feature: Guest Recognition Control Accompanied by Stepwise Gate Closing and Opening of a Macrocyclic Metallohost (Chem. Eur. J. 7/2021). Issue 7 (18th November 2020) - Sakata, Yoko; Okada, Masahiro; Akine, Shigehisa
Abstract : The recognition of a guest Na + ion significantly accelerated the AcO − ‐mediated gate‐opening of a closed dicobalt(III) macrocyclic metallohost [LCo2 (hda)2 ] 2+, which has two bridging 1, 6‐hexanediamine (hda) ligands, yielding an open host—guest complex [LCo2 (hda)2 (OAc)⋅ Na] 2+ . Since the closed complex [LCo2 (hda)2 ] 2+ was prepared by gate‐closing of an open complex, [LCo2 (pip)4 ] 2+ (pip=piperidine), the two‐step conversion efficiently controls the guest recognition behavior of the dicobalt metallohost. More information can be found in the Communication by S. Akine et al. on page 2284 .